CAPITALIZATION OF ASSETS AS THE “MYSTERY” BEHIND CAPITAL - Mulyani, Lilis (Jurnal Masyarakat dan Budaya, 2006)
Title of Book : The Mystery of Capital Author : Hernando de Soto Year Published : 2000 Number of pages : 276 pages